Employment impact of national, provincial and local government capital in South Africa: An aggregate and sectoral perspective - Charles Shaaba Saba; Nicholas Ngepah; Abieyuwa Ohonba (Cogent Economics & Finance, 2022)
This study examines the impact of general/national, provincial and local government capital on employment in South Africa. The study spans from 1993 to 2017 for a panel of 269 South African municipalities. The study employs the Granger causality test and the System Generalised Method of Moments (SGMM) estimation techniques. Findings show bidirectional causality between the variables of interest in the eight economic sectors. The results from the SGMM show that general/national government capital contributes more to total employment and the categories of employment (that is, different skills levels) in the economic sectors compared to provincial and local government capital. This suggests provincial and local government capital has not adequately contributed to citizens' different skills development and employment levels. Therefore, this article recommends synergised and well invested national, provincial and local government capital at all levels of skills development to equip citizens, create jobs, and grow the South African economy.
Keywords: 330; Government capital; employment; system-GMM; South Africa